2020
DOI: 10.1186/s13071-020-04437-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple insecticide resistance target sites in adult field strains of An. gambiae (s.l.) from southeastern Senegal

Abstract: Background High coverage of long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) are the cornerstones of vector control strategy in Senegal where insecticide resistance by the target vectors species is a great of concern. This study explores insecticide susceptibility profile and target-site mutations mechanisms within the Anophelesgambiae complex in southeastern Senegal. Methods Larvae of Anopheles spp. were col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…gambiae s.l. population from the surveyed area of Senegal, thus confirming reports from previous studies in the country [16,30]. However, over the study period and area, the mutation was only found in Anopheles gambiae s.s and An.…”
Section: Discussionsupporting
confidence: 90%
“…gambiae s.l. population from the surveyed area of Senegal, thus confirming reports from previous studies in the country [16,30]. However, over the study period and area, the mutation was only found in Anopheles gambiae s.s and An.…”
Section: Discussionsupporting
confidence: 90%
“…coluzzii especially in An . gambiae s.s. populations from the south-eastern part of the country [ 20 , 32 ]. The low frequency of Vgsc-1014F observed in An.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is exacerbated by the cross-resistance phenomenon and the emergence of multi-drug-resistant insect populations [ 11 , 12 ]. For instance, populations of the Anopheles, Culex, Aedes, and Culiseta mosquito genera with multiple resistance to four groups of insecticides (COCs, OPCs, pyrethroids, carbamates) were documented in Senegal in 2014 and in Iran in 2000–2020 [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%